2021
DOI: 10.1055/s-0040-1716936
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentration of Myelin Basic Protein as a Prognostic Marker in Mild-to-moderate Head Injury Patients: A Prospective Study in a Tertiary Care Center

Abstract: Objective To estimate the level of myelin basic protein (MBP) and look for its validity in outcome prediction among mild-to-moderate head injury patients. Materials and Methods It was a prospective study done at the Department of Neurosurgery, Institute of Medical Sciences, Banaras Hindu University from Jan 2018 to July 2019. All patients who presented to us within 48 hours of injury with mild-to-moderate head injury with apparently normal CT brain were include in the study. The serum sample were collected on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The blood is centrifuged for 30 min, then the serum is placed in barcoded aliquot containers, and stored in a freezer at −70 • C for transportation to a central laboratory. Thereafter, the samples are analyzed in batches using sandwich enzyme-linked immunosorbent assays (ELISA) to s100B [100][101][102], MBP [103][104][105] and NF-L [106][107][108] (R&D Systems). All reagents are prepared at room temperature.…”
Section: Oxidative Stress (S100b Mbp and Nf-l)mentioning
confidence: 99%
“…The blood is centrifuged for 30 min, then the serum is placed in barcoded aliquot containers, and stored in a freezer at −70 • C for transportation to a central laboratory. Thereafter, the samples are analyzed in batches using sandwich enzyme-linked immunosorbent assays (ELISA) to s100B [100][101][102], MBP [103][104][105] and NF-L [106][107][108] (R&D Systems). All reagents are prepared at room temperature.…”
Section: Oxidative Stress (S100b Mbp and Nf-l)mentioning
confidence: 99%
“… 13 Studies have shown that serum MBP is a prognostic marker of brain injury. 14 Additionally, changes in blood MBP levels may reflect the degree of glial injury in the central nervous system; however, few clinical studies have investigated whether changes in MBP may be an index for the development of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%